THE IMPACTS OF EXPERIENTIAL MARKETING AND PRODUCT FEATURES ON CUSTOMER SATISFACTION AND REPURCHASE INTENTION: A CASE STUDY OF IKEA - Naima, Fairuza; Fachira, Ira (Journal of Business and Management, 2018)
Abstract. Experiential marketing is an approach that encourages customer’s involvement in the process. It creates positive, memorable experiences that build a closer bond between customer and the brand. IKEA is a company that implements experiential strategy in their marketing approach that is known as IKEA shopping experience. However, besides the shopping experience, there are the product features that also determine the satisfaction and intention to repurchase. This study aims to explore the impact of experiential marketing compared to product features on customer satisfaction that will lead to the intention of repeat purchasing. Primary data were collected using online questionnaire with sample size of 141 respondents. The findings on this study confirm that experiential marketing has a positive and significant relationship with customer satisfaction and repurchase intention, product features has a positive and significant relationship with customer satisfaction, and customer satisfaction has a positive and significant relationship with repurchase intention. Furthermore, a mediation analysis was performed in this study to test the mediating effect of customer satisfaction on the relationship between product features and repurchase intention. However, the result shows that there is no mediating effect occurs. This study provides several recommendations for marketers in furnihing retail industry. On the other hand, a recommendation for future research is provided as well, regarding the discriminant validity establishment that needs dissimilarities between sets of indicators. Keywords: Customer satisfaction, experiential marketing, furnishing retail, product features, repurchase intention